Molecular gas in the halo fuels the growth of a massive cluster galaxy at high redshift - Emonts, Bjorn; Lehnert, M. D.; Villar-Martín, M.; Norris, R. P.; Ekers, R. D.; Moorsel, G. A. van; Dannerbauer, H.; Pentericci, L.; Miley, G. K.; Allison, J. R.; Sadler, E. M.; Guillard, P.; et al. (Science, 2016)
A massive galaxy forming from molecular gas - The most massive galaxies gather their stars by merging with smaller galaxies and by accreting gas, which is then consumed during star formation. Emonts et al. investigated the Spiderweb Galaxy, a massive galaxy in the process of forming in the early universe, seen now as it was over 10 billion years ago (see the Perspective by Hatch). Radio observations of carbon monoxide revealed large quantities of molecular gas around the galaxy. The gas is not associated with the merger process but may have been recycled from earlier phases of galaxy formation. - Science, this issue p. 1128; see also p. 1102 - The largest galaxies in the universe reside in galaxy clusters. Using sensitive observations of carbon monoxide, we show that the Spiderweb galaxy—a massive galaxy in a distant protocluster—is forming from a large reservoir of molecular gas. Most of this molecular gas lies between the protocluster galaxies and has low velocity dispersion, indicating that it is part of an enriched intergalactic medium. This may constitute the reservoir of gas that fuels the widespread star formation seen in earlier ultraviolet observations of the Spiderweb galaxy. Our results support the notion that giant galaxies in clusters formed from extended regions of recycled gas at high redshift. - The massive Spiderweb galaxy is surrounded by molecular gas as it goes through its formation process. - The massive Spiderweb galaxy is surrounded by molecular gas as it goes through its formation process.
Gesehen am 07.05.2020